Effect of Exercise Training on Left Ventricular Remodeling in Diabetic Patients with Diastolic Dysfunction: Rationale and Design. Issue 8 (January 2014) - Ul Haq, Muhammad Asrar; Wong, Chiew; Levinger, Itamar; Srivastava, Piyush M.; Sbaraglia, Melissa; Toia, Deidre; Jerums, George; Selig, Steve; Hare, David L.
Introduction: This study will examine the effects of combined aerobic and resistance training on left ventricular remodeling in diabetic patients with diastolic dysfunction. This is the first randomized controlled trial to look for effects of combined strength training and aerobic exercise on myocardial function as well as other clinical, functional, or psychological parameters in diabetic patients with isolated diastolic dysfunction, and will provide important insights into the potential management strategies for heart failure with preserved ejection fraction. Methods and Analysis: This is a prospective, randomized controlled investigator initiated single center trial. Diabetic patients with LV diastolic dysfunction suitable for exercise training intervention will be randomized to three months of a supervised combination of aerobic and strength training exercises, or supervised light stretching (control arm). Pre and post intervention assessment will include stress echocardiography, peak aerobic power with 12-lead ECG, dual-energy X-ray absorptiometry, muscle strength, the capacity to perform activities of daily living (ADLs), and questionnaires to assess self-perceived quality of life and symptoms of depression. The primary endpoint is to compare any change in tissue Doppler-derived LV systolic and early diastolic velocities. Ethics and Dissemination: The current trial protocol has been approved by the Human Research Ethics Committee of Austin Health and the University of Melbourne, Melbourne. The study will be performed in accordance with the Declaration of Helsinki. The investigator, regardless of the outcome, will publish the results of the study. Trial Registration: Australian New Zealand Clinical Trials Registry: ACTRN12610000943044.